3D Printing of Elastomeric Bioinspired Complex Adhesive Microstructures. Issue 40 (15th August 2021) - Dayan, Cem Balda; Chun, Sungwoo; Krishna‐Subbaiah, Nagaraj; Drotlef, Dirk‐Michael; Akolpoglu, Mukrime Birgul; Sitti, Metin
Abstract: Bioinspired elastomeric structural adhesives can provide reversible and controllable adhesion on dry/wet and synthetic/biological surfaces for a broad range of commercial applications. Shape complexity and performance of the existing structural adhesives are limited by the used specific fabrication technique, such as molding. To overcome these limitations by proposing complex 3D microstructured adhesive designs, a 3D elastomeric microstructure fabrication approach is implemented using two‐photon‐polymerization‐based 3D printing. A custom aliphatic urethane‐acrylate‐based elastomer is used as the 3D printing material. Two designs are demonstrated with two combined biological inspirations to show the advanced capabilities enabled by the proposed fabrication approach and custom elastomer. The first design focuses on springtail‐ and gecko‐inspired hybrid microfiber adhesive, which has the multifunctionalities of side‐surface liquid super‐repellency, top‐surface liquid super‐repellency, and strong reversible adhesion features in a single fiber array. The second design primarily centers on octopus‐ and gecko‐inspired hybrid adhesive, which exhibits the benefits of both octopus‐ and gecko‐inspired microstructured adhesives for strong reversible adhesion on both wet and dry surfaces, such as skin. This fabrication approach could be used to produce many other 3D complex elastomeric structural adhesives for future real‐world applications. Abstract : A 3D‐printing‐based fabrication approach is utilized for creating complex elastomeric microstructural adhesives directly. Two hybrid bioinspired structure designs are demonstrated, combining the strengths of gecko‐inspired microfiber adhesives with springtail‐ and octopus‐inspired microstructures to enable complex adhesives toward various real‐world applications.